2014
DOI: 10.31450/ukrjnd.1(45).2015.02
|View full text |Cite
|
Sign up to set email alerts
|

Immune Status of Patients With Chronic Obstructive Pulmonary Disease, Accompanied With Chronic Kidney Disease and Metabolic Disturbances

Abstract: The chronic kidney disease (CKD) is often accompanied to the chronic pulmonary disease (COPD) III stage and metabolic syndrome, (MS) which is because to the persistence of arterial hypertension and disturbances in hydrocarbon metabolism. Materials and methods. There were examined the 52 patients with III stage COPD, combined with MS, aged 51,3±4,2 years old, among them 23 with COPD, combined with MS and CKD I-IIstage (the main group). The compared group was included the 29 patients with COPD, combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The results of experimental and clinical scientific studies intensively performed during the last decade, revealed a new phenomenon: excessive body weight is accompanied by inflammation of adipose tissue, which occurs with its infiltration by immune cells. Moreover, the severity of this inflammation clearly correlates with the degree of obesity [1,2,11,13]. Since the inflammatory reaction occurs in tissue that is well-vascularized and inner-vated, the proportion of which can be up to 50% or more of the total body weight, therefore systemic manifestations should be expected [3,4,10].…”
Section: Problem Statement and Analysis Of The Latest Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of experimental and clinical scientific studies intensively performed during the last decade, revealed a new phenomenon: excessive body weight is accompanied by inflammation of adipose tissue, which occurs with its infiltration by immune cells. Moreover, the severity of this inflammation clearly correlates with the degree of obesity [1,2,11,13]. Since the inflammatory reaction occurs in tissue that is well-vascularized and inner-vated, the proportion of which can be up to 50% or more of the total body weight, therefore systemic manifestations should be expected [3,4,10].…”
Section: Problem Statement and Analysis Of The Latest Researchmentioning
confidence: 99%
“…They function both locally and systematically [9,15]. Leptin is one of the adipokines synthesized by the adipose tissue; it activates inflammation, promotes angiosteosis, initiates oxidative stress, increases the tone of sympathetic nervous system, changes cytokine regulation, which plays an important role in the pathogenesis of inflammatory damage [1,12,22].…”
Section: Problem Statement and Analysis Of The Latest Researchmentioning
confidence: 99%
See 1 more Smart Citation